Two-component aerosol spray paint and preparation method thereof

By using modified acrylate copolymers and modified multi-walled carbon nanotubes, combined with specific chemical modifications and combinations, the shortcomings of existing two-component aerosol spray paints in anti-corrosion, anti-UV aging, anti-bacterial and flame-retardant properties are solved , achieving more efficient metal surface protection and a wider range of applications.

CN119350937AActive Publication Date: 2025-01-24GUANGDONG HOSEN NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411530249.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing two-component aerosol spray paints have shortcomings in preventing metal surface corrosion and resisting UV aging, and lack antibacterial and flame retardant properties.

Method used

The modified acrylate cluster and modified multi -wall carbon nanotubes are used as the main ingredient, and through specific chemical modification and combination, it forms a dual -group gas mist paint with anti -corrosion, anti -ultraviolet aging, antibacterial and flame retardant properties.

Benefits of technology

It significantly improves the anticorrosive and ultraviolet aging performance of spray paint, and gives antibacterial and flame retardant performance, extending the service life and safety of the coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses two-component aerosol spray paint and a preparation method thereof, and relates to the field of spray paint. The prepared two-component aerosol spray paint comprises a component A and a component B. The component A comprises a modified acrylate copolymer, modified multi-walled carbon nanotubes, an environment-friendly solvent, a rheological additive, a leveling agent, a propellant and hydroxy acrylic resin, and the component B comprises an isocyanate curing agent and a solvent. Wherein the modified acrylate copolymer is prepared by the following steps: initiating methyl methacrylate, n-butyl acrylate and dimethylallylamine by an initiator to obtain an acrylate copolymer, reacting with chloromethyl (methyl) phosphoryl chloride, reacting with 5-amino-2-chloropyrimidine, reacting with 3-methoxy-2-(tributyltin alkyl) pyridine, reacting with 2-chloro-3-(tributyltin alkyl) pyridine, and reacting with 2-chloro-3-(tributyltin alkyl) pyridine to obtain the modified acrylate copolymer. And finally, demethylating through boron tribromide to obtain the product. The modified multi-walled carbon nanotubes are obtained by grafting acylating chlorination multi-walled carbon nanotubes with chitosan, oxidizing the acylating chlorination multi-walled carbon nanotubes with sodium periodate and then reacting the oxidized acylating chlorination multi-walled carbon nanotubes with 2-amino-4, 6-di-tert-butylphenol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of spray paint, in particular to a two-component aerosol spray paint and a preparation method thereof. Background Art

[0002] Two-component aerosol spray paint is an important product type in the current coatings field. There are many types of paints on the market, mainly including one-component paint and two-component paint. One-component paint generally does not require cross-linking and curing. It usually has only one package and is ready to use and forms a film directly. This type of paint is simple to operate, but its performance is relatively limited.

[0003] Two-component paint is a coating made of a mixture of two different ingredients, one of which is a base coating and the other is a curing agent. Although two-component paint is superior to single-component paint in performance, there are still some shortcomings in the two-component aerosol spray paint currently on the market. For example, for spray paint used on metal surfaces, the coating formed by the spray paint needs to be able to prevent moisture and oxygen in the air from invading the metal surface and causing metal corrosion; coatings used outdoors for a long time are very likely to age and crack under ultraviolet light, thereby causing a decrease in coating performance. Therefore, in order to overcome these shortcomings, it is particularly important to develop two-component aerosol spray paints with anti-corrosion and anti-ultraviolet aging properties. In addition, the spray paint can also be given antibacterial and flame retardant properties, which can broaden the application scope of two-component spray paints while preventing microbial erosion and improving safety to meet the different needs of users. Summary of the invention

[0004] The object of the present invention is to provide a two-component aerosol spray paint and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A two-component aerosol spray paint, comprising component A and component B, wherein component A comprises a modified acrylate copolymer, modified multi-walled carbon nanotubes, an environmentally friendly solvent, a rheological additive, a leveling agent, a propellant, and a hydroxy acrylic resin; and component B comprises an isocyanate curing agent and a solvent;

[0007] As an optimization, the modified acrylate copolymer is obtained by reacting methyl methacrylate, n-butyl acrylate and dimethylallylamine under the initiation of an initiator to obtain an acrylate copolymer, reacting the acrylate copolymer with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer; then reacting with 5-amino-2-chloropyrimidine to obtain a chloropyrimidinyl acrylate copolymer, then reacting with 3-methoxy-2-(tributylstannyl)pyridine to obtain a pre-modified acrylate copolymer, and finally demethylating the copolymer with boron tribromide to obtain the copolymer.

[0008] As an optimization, the modified multi-walled carbon nanotubes are obtained by grafting chitosan onto acyl chloride multi-walled carbon nanotubes, oxidizing with sodium periodate, and reacting with 2-amino-4,6-di-tert-butylphenol.

[0009] A method for preparing a two-component aerosol spray paint comprises the following preparation steps:

[0010] (1) Methyl methacrylate, n-butyl acrylate, dimethylallylamine, and toluene are mixed in a mass ratio of 0.5:4:5.5:(20-30), heated to 80-90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuum at 80° C. for 24 hours to obtain an acrylate polymer;

[0011] (2) mixing an acrylate polymer, triethylamine, chloromethyl (methyl) phosphinoyl chloride, and dichloromethane in a mass ratio of 1: (0.3-0.5): (0.8-0.9): (20-30), heating to 70-80° C., reacting for 12 hours, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, drying the organic layer in air at 45° C. for 12 hours, and then vacuum drying at 50° C. for 20 hours to obtain a quaternized acrylate copolymer;

[0012] (3) Weighing a quaternary ammonium acrylate copolymer and 5-amino-2-chloropyrimidine in a mass ratio of 1:(1-1.2), mixing the quaternary ammonium acrylate copolymer and dichloromethane in a mass ratio of 1:(20-30) to obtain a quaternary ammonium acrylate copolymer solution, mixing 5-amino-2-chloropyrimidine, triethylamine, and dichloromethane in a mass ratio of 1:(1.2-1.3):(10-12) to obtain a 5-amino-2-chloropyrimidine solution, and adding the 5-amino-2-chloropyrimidine solution dropwise to the quaternary ammonium acrylate copolymer solution at a dropping rate of 1 mL / min. After the dropping is completed, the reaction is continued for 2-3 hours, and a 10 wt % hydrochloric acid solution of 10-12 times the mass of the quaternary ammonium acrylate copolymer is added, and then a saturated sodium bicarbonate solution of 10-12 times the mass of the quaternary ammonium acrylate copolymer is added, and the organic phase is taken and vacuum rotary evaporated to obtain a chloropyrimidinyl acrylate copolymer;

[0013] (4) 3-methoxy-2-(tributyltinyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.3-0.5):(0.1-0.2):(10-12) and degassed, and 0.1-0.2 times the mass of 3-methoxy-2-(tributyltinyl)pyridine tetrakis(triphenylphosphine)palladium(0) is added, and the temperature is raised to 100° C. to react for 16-18 hours. After the reaction is completed, the pre-modified acrylate copolymer is obtained by rotary evaporation under reduced pressure;

[0014] (5) Under argon protection, anhydrous and oxygen-free conditions, the pre-modified acrylate copolymer and dichloromethane are mixed in a mass ratio of 1:(50-60), cooled to -20°C, and 0.3-0.5 times the volume of the pre-modified acrylate copolymer of boron tribromide is added dropwise at a rate of 0.5 mL / min. After the addition is completed, the reaction is continued at -20°C for 12 hours. After the reaction is completed, methanol with a volume of 0.1 times that of dichloromethane is added, and then an ice-water mixture with a mass of 3-4 times that of dichloromethane is added, filtered and vacuum dried at 50°C for 20 hours to obtain a modified acrylate copolymer;

[0015] (6) Pre-modified multi-walled carbon nanotubes, 2-amino-4,6-di-tert-butylphenol, and anhydrous ethanol were mixed in a mass ratio of 1:(4-5):(50-60), refluxed at 78°C for 5-6 hours, cooled to room temperature after the reaction, filtered, washed with anhydrous ethanol for 3-4 times, and finally vacuum dried at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes;

[0016] (7) Weigh 15-20 parts by mass of a modified acrylate copolymer, 3-5 parts by mass of a modified multi-walled carbon nanotube, 30-40 parts by mass of an environmentally friendly solvent, 0.1-0.5 parts by mass of a rheological aid, 0.1-0.5 parts by mass of a leveling agent, 20-25 parts by mass of a propellant, and 20 parts by mass of a hydroxy acrylic resin; stir the modified acrylate copolymer, modified multi-walled carbon nanotube, environmentally friendly solvent, rheological aid, leveling agent, and hydroxy acrylic resin evenly and grind to a fineness of ≤45 μm, and after grinding, put them into the liquid feed end of a two-component aerosol can, continue to add the propellant and seal the can to obtain component A; weigh 3-5 parts by mass of an isocyanate curing agent and 20-30 parts by mass of a solvent, stir the isocyanate curing agent and the solvent evenly, and after stirring, put them into the curing agent end of a two-component aerosol can and seal the can to obtain component B, press the curing agent end and shake to mix evenly, and obtain a two-component aerosol spray paint.

[0017] As an optimization, the initiator solution in step (1) comprises ammonium persulfate and pure water, wherein the mass ratio of ammonium persulfate to pure water is 1:20.

[0018] As an optimization, the preparation method of the pre-modified multi-walled carbon nanotubes in step (6) is as follows: multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7-8 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5-6 times, and dried at 50-60°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan is dispersed in N,N-dimethylformamide with a mass of 30 times that of chitosan, allowed to stand for 12h, and chitosan is added under nitrogen protection. The invention discloses a method for preparing chitosan grafted multi-walled carbon nanotubes by preparing a mixture of chitosan grafted multi-walled carbon nanotubes and preparing the mixture of chitosan grafted multi-walled carbon nanotubes. The mixture is ultrasonically treated for 2 hours and then reacted for 96 hours. After the reaction is completed, the mixture is filtered and washed with a 2wt% acetic acid solution for 3 times, filtered with a 0.2μm microporous filter membrane, and finally vacuum dried at 60°C for 12 hours to obtain chitosan grafted multi-walled carbon nanotubes. The chitosan grafted multi-walled carbon nanotubes and an acetic acid buffer solution with a pH of 3 are mixed in a mass ratio of 1:80, and under nitrogen protection, a sodium periodate aqueous solution with a mass of 5-6 times that of the chitosan grafted multi-walled carbon nanotubes is added, and the mixture is reacted at 4°C for 44-48 hours, filtered and washed with pure water for 3-4 times, and finally vacuum dried at 60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes.

[0019] As an optimization, the multi-walled carbon nanotube model is L-MWNT-1020; the deacetylation degree of the chitosan is ≥95%.

[0020] As an optimization, the sodium periodate aqueous solution is prepared by mixing sodium periodate and water in a mass ratio of 1:20.

[0021] As an optimization, the model of the hydroxy acrylic resin in step (7) is HU56024; the environmentally friendly solvent is propylene glycol ether acetate; the model of the isocyanate curing agent is Basonat HB100; the model of the leveling agent is YCK-1270N; the model of the rheological additive is BYK-7410; the model of the propellant is HFC-134a; and the solvent is acetone.

[0022] The beneficial effects of the present invention are as follows:

[0023] In the preparation of the two-component aerosol spray paint, first, methyl methacrylate, n-butyl acrylate and dimethylallylamine are reacted with an initiator to obtain an acrylate copolymer, and the acrylate copolymer is reacted with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer; the acrylate copolymer is reacted with 5-amino-2-chloropyrimidine to obtain a chloropyrimidyl acrylate copolymer, and the quaternized acrylate copolymer is reacted with 3-methoxy-2-(tributylstannyl)pyridine to obtain a pre-modified acrylate copolymer, and finally the modified acrylate copolymer is demethylated with boron tribromide to obtain a pre-modified acrylate copolymer. Acrylate copolymer; secondly, grafting chitosan with acyl chloride multi-walled carbon nanotubes, oxidizing with sodium periodate and reacting with 2-amino-4,6-di-tert-butylphenol to obtain modified multi-walled carbon nanotubes; finally, loading the modified acrylate copolymer, modified multi-walled carbon nanotubes, environmentally friendly solvent, rheological additive, leveling agent, propellant and hydroxyl acrylic resin into the feed liquid end of a two-component aerosol can, loading the isocyanate curing agent and solvent into the curing agent end of the two-component aerosol can, pressing the curing agent end button and shaking to mix evenly to obtain a two-component aerosol spray paint.

[0024] Firstly, methyl methacrylate, n-butyl acrylate and dimethylallylamine are induced by an initiator to obtain an acrylate copolymer, wherein the dimethylallylamine makes the side chain of the acrylate copolymer have a tertiary amine structure, the acrylate copolymer is reacted with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternary ammonium acrylate copolymer, the chloromethyl on the chloromethyl (methyl) phosphinoyl chloride reacts with the tertiary amine to form a quaternary ammonium salt with antibacterial properties, which can give the spray paint antibacterial properties, and the introduction of phosphorus elements can give the spray paint flame retardant properties, the phosphoramide group on the quaternary ammonium acrylate copolymer is then subjected to an amidation reaction with the amino group on 5-amino-2-chloropyrimidine to obtain a chloropyrimidinyl acrylate copolymer, and then The pre-modified acrylate copolymer is obtained by reacting with 3-methoxy-2-(tributyltin alkyl) pyridine, the methoxypyridine functional group on the 3-methoxy-2-(tributyltin alkyl) pyridine is grafted onto 5-amino-2-chloropyrimidine, and finally the modified acrylate copolymer is obtained by demethylation with boron tribromide. Boron tribromide removes the methyl group on the 3-methoxy-2-(tributyltin alkyl) pyridine to generate a hydroxyl group. The hydroxyl group is located at the ortho position of the nitrogen element on the pyrimidine group and can form an intramolecular chelate ring with the nitrogen element. When subjected to ultraviolet irradiation, the light energy is converted into heat energy and dissipated, thereby improving the anti-ultraviolet aging performance of the material; the divalent structure formed by pyridine and pyrimidine has a good complexing effect on metals.

[0025] Secondly, the acyl chloride multi-walled carbon nanotubes are grafted with chitosan. The multi-walled carbon nanotubes have excellent conductivity. When they are uniformly dispersed in the coating, good electrochemical contact will form a conductive network, which greatly enhances the electrochemical protection ability of the coating. It can also form a shielding structure in the coating formed by spray painting, effectively preventing the penetration and diffusion of corrosive media and improving the physical anti-corrosion properties of the coating; chitosan, as a natural polysaccharide, has good hydrophilicity and adhesion, which can enhance the affinity between the spray paint and the substrate. Chitosan is oxidized by sodium periodate to form a dialdehyde group, and the dialdehyde group reacts with 2-amino-4,6-di-tert-butylphenol to form a Schiff base to obtain modified multi-walled carbon nanotubes; the Schiff base and the adjacent hydroxyl group have a good complexing effect on metal ions.

[0026] Finally, the modified acrylate copolymer, modified multi-walled carbon nanotubes, environmentally friendly solvent, rheological additive, leveling agent, hydroxy acrylic resin and propellant are loaded into the liquid feed end of the two-component aerosol can, and the isocyanate curing agent and solvent are loaded into the curing agent end of the two-component aerosol can, and the curing agent end is pressed and shaken to mix evenly to obtain a two-component aerosol spray paint; the metal ligands on the modified acrylate copolymer and the modified multi-walled carbon nanotubes can be coordinated and complexed with metal ions. For metal substrates, they can undergo physical and chemical adsorption with the metal substrate before corrosion occurs, forming a dense protective film on the surface of the substrate, which plays a more excellent physical barrier role. During the corrosion process, they can undergo chelation reaction with free metal ions to generate stable organic chelates. Such organic chelates have good compatibility with the coating and are not prone to phase separation, thereby delaying further corrosion. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The initiator solution used in the following embodiments and comparative examples is prepared by mixing ammonium persulfate and pure water in a mass ratio of 1:20; the multi-walled carbon nanotube model used is L-MWNT-1020; the deacetylation degree of the chitosan used is ≥95%; the sodium periodate solution used is prepared by mixing sodium periodate and water in a mass ratio of 1:20; the model of the hydroxylated acrylic resin used is HU56024; the environmentally friendly solvent used is propylene glycol ether acetate; the model of the isocyanate curing agent used is Basonat HB100; the model of the leveling agent used is YCK-1270N; the model of the rheological additive used is BYK-7410; the model of the propellant used is HFC-134a; and the solvent used is acetone.

[0029] Embodiment 1:

[0030] A method for preparing a two-component aerosol spray paint, the method comprising the following steps:

[0031] (1) Methyl methacrylate, n-butyl acrylate, dimethylallylamine, and toluene are mixed in a mass ratio of 0.5:4:5.5:20, heated to 90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuum at 80° C. for 24 hours to obtain an acrylate polymer;

[0032] (2) mixing an acrylate polymer, triethylamine, chloromethyl (methyl) phosphinoyl chloride, and dichloromethane in a mass ratio of 1:0.3:0.8:20, heating to 80° C., reacting for 12 h, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, taking an organic layer and drying it in air at 45° C. for 12 h, and then vacuum drying it at 50° C. for 20 h to obtain a quaternized acrylate copolymer;

[0033] (3) Weighing a quaternary ammonium acrylate copolymer and 5-amino-2-chloropyrimidine in a mass ratio of 1:1, mixing the quaternary ammonium acrylate copolymer and dichloromethane in a mass ratio of 1:20 to obtain a quaternary ammonium acrylate copolymer solution, mixing 5-amino-2-chloropyrimidine, triethylamine, and dichloromethane in a mass ratio of 1:1.2:10 to obtain a 5-amino-2-chloropyrimidine solution, and adding the 5-amino-2-chloropyrimidine solution dropwise to the quaternary ammonium acrylate copolymer solution at a dropping rate of 1 mL / min. After the dropping is completed, the reaction is continued for 3 hours, and a 10 wt% hydrochloric acid solution of 10 times the mass of the quaternary ammonium acrylate copolymer is added, and then a saturated sodium bicarbonate solution of 10 times the mass of the quaternary ammonium acrylate copolymer is added, and the organic phase is taken and vacuum rotary evaporated to obtain a chloropyrimidinyl acrylate copolymer;

[0034] (4) 3-methoxy-2-(tributyltinyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.3:0.1:10 and degassed, and 0.1 times the mass of 3-methoxy-2-(tributyltinyl)pyridine was added with tetrakis(triphenylphosphine)palladium(0), and the temperature was raised to 100° C. for reaction for 18 hours. After the reaction was completed, the pre-modified acrylate copolymer was obtained by vacuum rotary evaporation;

[0035] (5) Under argon protection, anhydrous and oxygen-free conditions, the pre-modified acrylate copolymer and dichloromethane were mixed at a mass ratio of 1:50, cooled to -20°C, and 0.3 times the volume of boron tribromide of the pre-modified acrylate copolymer was added dropwise at a rate of 0.5 mL / min. After the addition was completed, the reaction was continued at -20°C for 12 hours. After the reaction was completed, methanol with a volume of 0.1 times that of dichloromethane was added, and then an ice-water mixture with a mass of 3 times that of dichloromethane was added, filtered and vacuum dried at 50°C for 20 hours to obtain a modified acrylate copolymer;

[0036] (6) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and washed with pure water 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran 6 times, and dried at 60°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan was dispersed in N,N-dimethylformamide with a mass of 30 times that of chitosan, allowed to stand for 12h, and chlorinated multi-walled carbon nanotubes with a mass of 0.3 times that of chitosan were added under nitrogen protection, ultrasonically treated for 2h, and continued to react for 96h. After the reaction was completed, it was filtered and washed with 2wt% acetic acid solution 3 times, and 0.2μm The mixture was filtered through a microporous membrane, and finally vacuum dried at 60°C for 12 hours to obtain chitosan grafted multi-walled carbon nanotubes; chitosan grafted multi-walled carbon nanotubes and acetic acid buffer solution with a pH of 3 were mixed in a mass ratio of 1:80, and under nitrogen protection, a sodium periodate aqueous solution with a mass of 5 times that of the chitosan grafted multi-walled carbon nanotubes was added, and the mixture was reacted at 4°C for 48 hours, filtered and washed with pure water for 4 times, and finally vacuum dried at 60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes; pre-modified multi-walled carbon nanotubes, 2-amino-4,6-di-tert-butylphenol, and anhydrous ethanol were mixed in a mass ratio of 1:4:50, refluxed at 78°C for 6 hours, and after the reaction was completed, cooled to room temperature, filtered and washed with anhydrous ethanol for 4 times, and finally vacuum dried at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes;

[0037] (7) Weigh 15 parts of modified acrylate copolymer, 3 parts of modified multi-walled carbon nanotubes, 30 parts of environmentally friendly solvent, 0.1 parts of rheological additive, 0.1 parts of leveling agent, 20 parts of hydroxy acrylic resin, and 20 parts of propellant by weight; stir the modified acrylate copolymer, modified multi-walled carbon nanotubes, environmentally friendly solvent, rheological additive, leveling agent, and hydroxy acrylic resin evenly and grind to a fineness of ≤45 μm. After grinding, put them into the liquid feed end of a two-component aerosol can, continue to add the propellant and seal it to obtain component A; weigh 3 parts of isocyanate curing agent and 20 parts of solvent by weight, stir the isocyanate curing agent and solvent evenly, put them into the curing agent end of the two-component aerosol can and seal it to obtain component B, press the curing agent end and shake it to mix evenly, and obtain a two-component aerosol spray paint.

[0038] Embodiment 2:

[0039] A method for preparing a two-component aerosol spray paint, the method comprising the following steps:

[0040] (1) Methyl methacrylate, n-butyl acrylate, dimethylallylamine, and toluene are mixed in a mass ratio of 0.5:4:5.5:25, heated to 85° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuum at 80° C. for 24 hours to obtain an acrylate polymer;

[0041] (2) mixing an acrylate polymer, triethylamine, chloromethyl (methyl) phosphinoyl chloride, and dichloromethane in a mass ratio of 1:0.4:0.85:25, heating to 75° C., reacting for 12 h, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, taking an organic layer and drying it in air at 45° C. for 12 h, and then vacuum drying it at 50° C. for 20 h to obtain a quaternized acrylate copolymer;

[0042] (3) Weighing a quaternary ammonium acrylate copolymer and 5-amino-2-chloropyrimidine in a mass ratio of 1:1.1, mixing the quaternary ammonium acrylate copolymer and dichloromethane in a mass ratio of 1:25 to obtain a quaternary ammonium acrylate copolymer solution, mixing 5-amino-2-chloropyrimidine, triethylamine, and dichloromethane in a mass ratio of 1:1.25:11 to obtain a 5-amino-2-chloropyrimidine solution, and adding the 5-amino-2-chloropyrimidine solution dropwise to the quaternary ammonium acrylate copolymer solution at a dropping rate of 1 mL / min. After the dropping is completed, the reaction is continued for 2.5 hours, and a 10 wt % hydrochloric acid solution of 11 times the mass of the quaternary ammonium acrylate copolymer is added, and then a saturated sodium bicarbonate solution of 11 times the mass of the quaternary ammonium acrylate copolymer is added, and the organic phase is taken and vacuum rotary evaporated to obtain a chloropyrimidinyl acrylate copolymer;

[0043] (4) 3-methoxy-2-(tributyltinyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.4:0.15:11 and degassed, and 0.15 times the mass of 3-methoxy-2-(tributyltinyl)pyridine was added with tetrakis(triphenylphosphine)palladium(0), and the temperature was raised to 100° C. for reaction for 17 hours. After the reaction was completed, the pre-modified acrylate copolymer was obtained by vacuum rotary evaporation;

[0044] (5) Under argon protection, anhydrous and oxygen-free conditions, the pre-modified acrylate copolymer and dichloromethane were mixed in a mass ratio of 1:55, cooled to -20°C, and 0.4 times the volume of boron tribromide of the pre-modified acrylate copolymer was added dropwise at a rate of 0.5 mL / min. After the addition was completed, the reaction was continued at -20°C for 12 hours. After the reaction was completed, methanol with a volume of 0.1 times that of dichloromethane was added, and then an ice-water mixture with a mass of 3.5 times that of dichloromethane was added, filtered and vacuum dried at 50°C for 20 hours to obtain a modified acrylate copolymer;

[0045] (6) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5 times, and dried at 55°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan was dispersed in N,N-dimethylformamide with a mass of 30 times that of chitosan, allowed to stand for 12h, and chlorinated multi-walled carbon nanotubes with a mass of 0.4 times that of chitosan were added under nitrogen protection, ultrasonically treated for 2h, and continued to react for 96h. After the reaction was completed, it was filtered and washed with 2wt% acetic acid solution for 3 times, and a 0.2μm microporous Filter the mixture with a filter membrane, and finally vacuum dry it at 60°C for 12 hours to obtain chitosan-grafted multi-walled carbon nanotubes; mix the chitosan-grafted multi-walled carbon nanotubes and an acetic acid buffer solution with a pH of 3 at a mass ratio of 1:80, add a sodium periodate aqueous solution with a mass of 5.5 times that of the chitosan-grafted multi-walled carbon nanotubes under nitrogen protection, react at 4°C for 45 hours, filter and wash with pure water three times, and finally vacuum dry it at 60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes; mix the pre-modified multi-walled carbon nanotubes, 2-amino-4,6-di-tert-butylphenol, and anhydrous ethanol at a mass ratio of 1:4.5:55, reflux at 78°C for 5.5 hours, cool to room temperature after the reaction, filter and wash with anhydrous ethanol three times, and finally vacuum dry it at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes;

[0046] (7) Weigh 17 parts by mass of a modified acrylic copolymer, 4 parts by mass of a modified multi-walled carbon nanotube, 35 parts by mass of an environmentally friendly solvent, 0.3 parts by mass of a rheological aid, 0.3 parts by mass of a leveling agent, 20 parts by mass of a hydroxy acrylic resin, and 23 parts by mass of a propellant; stir the modified acrylic copolymer, modified multi-walled carbon nanotube, environmentally friendly solvent, rheological aid, leveling agent, and hydroxy acrylic resin, and grind them to a fineness of ≤45 μm. After grinding, put them into the liquid feed end of a two-component aerosol can, continue to add the propellant, and seal the can to obtain component A; weigh 4 parts by mass of an isocyanate curing agent and 25 parts by mass of a solvent, stir the isocyanate curing agent and the solvent, and after stirring, put them into the curing agent end of a two-component aerosol can and seal the can to obtain component B. Press the curing agent end and shake to mix evenly to obtain a two-component aerosol spray paint.

[0047] Embodiment 3:

[0048] A method for preparing a two-component aerosol spray paint, the method comprising the following steps:

[0049] (1) Methyl methacrylate, n-butyl acrylate, dimethylallylamine, and toluene are mixed in a mass ratio of 0.5:4:5.5:30, heated to 80° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuum at 80° C. for 24 hours to obtain an acrylate polymer;

[0050] (2) mixing an acrylate polymer, triethylamine, chloromethyl (methyl) phosphinoyl chloride, and dichloromethane in a mass ratio of 1:0.5:0.9:30, heating to 70° C., reacting for 12 h, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, taking an organic layer and drying it in air at 45° C. for 12 h, and then vacuum drying it at 50° C. for 20 h to obtain a quaternized acrylate copolymer;

[0051] (3) Weighing a quaternary ammonium acrylate copolymer and 5-amino-2-chloropyrimidine in a mass ratio of 1:1.2, mixing the quaternary ammonium acrylate copolymer and dichloromethane in a mass ratio of 1:30 to obtain a quaternary ammonium acrylate copolymer solution, mixing 5-amino-2-chloropyrimidine, triethylamine, and dichloromethane in a mass ratio of 1:1.3:12 to obtain a 5-amino-2-chloropyrimidine solution, and adding the 5-amino-2-chloropyrimidine solution dropwise to the quaternary ammonium acrylate copolymer solution at a dropping rate of 1 mL / min. After the dropping is completed, the reaction is continued for 2 h, and a 10 wt % hydrochloric acid solution of 12 times the mass of the quaternary ammonium acrylate copolymer is added, and then a saturated sodium bicarbonate solution of 12 times the mass of the quaternary ammonium acrylate copolymer is added, and the organic phase is taken and vacuum rotary evaporated to obtain a chloropyrimidinyl acrylate copolymer;

[0052] (4) 3-methoxy-2-(tributyltinyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.5:0.2:12 and degassed, and 0.2 times the mass of 3-methoxy-2-(tributyltinyl)pyridine was added with tetrakis(triphenylphosphine)palladium(0), and the temperature was raised to 100° C. for reaction for 16 hours. After the reaction was completed, the pre-modified acrylate copolymer was obtained by vacuum rotary evaporation;

[0053] (5) Under argon protection, anhydrous and oxygen-free conditions, the pre-modified acrylate copolymer and dichloromethane were mixed at a mass ratio of 1:60, cooled to -20°C, and 0.5 times the volume of boron tribromide of the pre-modified acrylate copolymer was added dropwise at a rate of 0.5 mL / min. After the addition was completed, the reaction was continued at -20°C for 12 hours. After the reaction was completed, methanol with a volume of 0.1 times that of dichloromethane was added, and then an ice-water mixture with a mass of 3 times that of dichloromethane was added, filtered and vacuum dried at 50°C for 20 hours to obtain a modified acrylate copolymer;

[0054] (6) Multi-walled carbon nanotubes and 68wt% concentrated nitric acid were mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and washed with pure water 7 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride were mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran 5 times, and dried at 50°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan was dispersed in N,N-dimethylformamide with a mass of 30 times that of chitosan, allowed to stand for 12h, and chlorinated multi-walled carbon nanotubes with a mass of 0.5 times that of chitosan were added under nitrogen protection, ultrasonically treated for 2h, and continued to react for 96h. After the reaction was completed, it was filtered and washed with 2wt% acetic acid solution 3 times, and 0.2μm The mixture was filtered through a microporous membrane, and finally vacuum dried at 60°C for 12 hours to obtain chitosan grafted multi-walled carbon nanotubes; chitosan grafted multi-walled carbon nanotubes and acetic acid buffer solution with a pH of 3 were mixed in a mass ratio of 1:80, and under nitrogen protection, a sodium periodate aqueous solution with a mass of 6 times that of the chitosan grafted multi-walled carbon nanotubes was added, and the mixture was reacted at 4°C for 44 hours, filtered and washed with pure water for 3 times, and finally vacuum dried at 60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes; pre-modified multi-walled carbon nanotubes, 2-amino-4,6-di-tert-butylphenol, and anhydrous ethanol were mixed in a mass ratio of 1:5:60, refluxed at 78°C for 5 hours, and after the reaction was completed, cooled to room temperature, filtered and washed with anhydrous ethanol for 3 times, and finally vacuum dried at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes;

[0055] (7) Weigh 20 parts of modified acrylate copolymer, 5 parts of modified multi-walled carbon nanotubes, 40 parts of environmentally friendly solvent, 0.5 parts of rheological additive, 0.5 parts of leveling agent, 20 parts of hydroxy acrylic resin, and 25 parts of propellant by weight; stir the modified acrylate copolymer, modified multi-walled carbon nanotubes, environmentally friendly solvent, rheological additive, leveling agent, and hydroxy acrylic resin evenly and grind to a fineness of ≤45 μm. After grinding, put them into the liquid feed end of a two-component aerosol can, continue to add the propellant and seal it to obtain component A; weigh 5 parts of isocyanate curing agent and 30 parts of solvent by weight, stir the isocyanate curing agent and solvent evenly, put them into the curing agent end of the two-component aerosol can and seal it to obtain component B, press the curing agent end and shake it to mix evenly, and obtain a two-component aerosol spray paint.

[0056] Comparative Example 1:

[0057] The preparation method of the two-component aerosol spray paint of Comparative Example 1 differs from that of Example 2 in that it does not contain steps (2), (3), (4) and (5), and step (1) is modified as follows: methyl methacrylate, n-butyl acrylate, dimethylallylamine and toluene are mixed in a mass ratio of 0.5:4:5.5:25, heated to 85°C under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuo at 80°C for 24 hours to obtain a modified acrylate polymer.

[0058] Comparative Example 2:

[0059] The preparation method of the two-component aerosol spray paint of Comparative Example 2 differs from that of Example 2 in that step (5) is not included, and step (4) is modified as follows: 3-methoxy-2-(tributyltinalkyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide are mixed in a mass ratio of 1:0.4:0.15:11 and degassed, and 0.15 times the mass of 3-methoxy-2-(tributyltinalkyl)pyridine is added with tetrakis(triphenylphosphine)palladium(0), the temperature is raised to 100° C. and the reaction is carried out for 17 hours. After the reaction is completed, the modified acrylate copolymer is obtained by rotary evaporation under reduced pressure.

[0060] Comparative Example 3:

[0061] The difference between the preparation method of the two-component aerosol spray paint of Comparative Example 3 and Example 2 is that step (6) is modified as follows: the multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water 7 times to obtain carboxylated multi-walled carbon nanotubes; the carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered and washed with tetrahydrofuran 5 times, and dried at 55°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan is dispersed in N,N-dimethylformamide 30 times the mass of chitosan, allowed to stand for 12h, and dried under nitrogen protection. , add 0.4 times the mass of chitosan to chlorinated multi-walled carbon nanotubes, ultrasonically treat for 2 hours, continue to react for 96 hours, after the reaction is completed, filter and wash with 2wt% acetic acid solution for 3 times, filter with 0.2μm microporous filter membrane, and finally vacuum dry at 60℃ for 12 hours to obtain chitosan grafted multi-walled carbon nanotubes; mix the chitosan grafted multi-walled carbon nanotubes and acetic acid buffer solution with pH 3 in a mass ratio of 1:80, add 5.5 times the mass of chitosan grafted multi-walled carbon nanotubes sodium periodate aqueous solution under nitrogen protection, react at 4℃ for 45 hours, filter and wash with pure water for 3 times, and finally vacuum dry at 60℃ for 12 hours to obtain modified multi-walled carbon nanotubes.

[0062] Test Example 1:

[0063] Water resistance test:

[0064] The two-component aerosol spray paints prepared in the examples and comparative examples were made into samples according to GB / T 9271-2008, and the water resistance of the samples was measured according to GB / T9274-1988. The samples were placed in a 25°C constant temperature water tank with 1 / 3 of the length exposed to the liquid surface. When the samples began to bubble, fall off, or corrode, the time was recorded. The results are shown in Table 1.

[0065] Anti-ultraviolet aging performance test:

[0066] The sample was made according to GB / T 9271-2008. The thickness of the sample paint film was 18μm. The sample was placed in a UV aging box. When the sample was bubbling, falling off, or corroded, the time was recorded. The temperature in the UV aging box was 50℃, the wavelength of the UV light was 340nm, the light power was 40W, and the distance between the paint film and the light source was 50mm. The results are shown in Table 1.

[0067] Table 1 Test results of water resistance and UV aging resistance

[0068] Water resistance / d Anti-ultraviolet aging / d Example 1 15 32 Example 2 14 32 Example 3 15 32 Comparative Example 1 10 25 Comparative Example 2 12 25 Comparative Example 3 10 30

[0069] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the two-component aerosol spray paint prepared in the present invention has good water resistance and anti-ultraviolet aging performance.

[0070] By comparison, the water resistance of Examples 1 to 3 is better than that of Comparative Examples 1 and 3, and the UV aging resistance of Examples 1 to 3 is better than that of Comparative Examples 1 to 2, which shows that first, methyl methacrylate, n-butyl acrylate, and dimethylallylamine are induced by an initiator to obtain an acrylate copolymer, the acrylate copolymer is reacted with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer, the phosphoramide group on the quaternized acrylate copolymer is further amidated with the amino group on 5-amino-2-chloropyrimidine to obtain a chloropyrimidyl acrylate copolymer, and then reacted with 3-methoxy-2-(tributylstannane) to obtain a quaternized acrylate copolymer. The pre-modified acrylate copolymer is obtained by reacting 3-methoxy-2-(tributyltinyl)pyridine, the methoxypyridine functional group on 3-methoxy-2-(tributyltinyl)pyridine is grafted onto 5-amino-2-chloropyrimidine, and finally the modified acrylate copolymer is obtained by demethylation with boron tribromide. Boron tribromide removes the methyl group on 3-methoxy-2-(tributyltinyl)pyridine to generate a hydroxyl group. The hydroxyl group is located at the ortho position of the nitrogen element on the pyrimidine group and can form an intramolecular chelate ring with the nitrogen element. When subjected to ultraviolet irradiation, the light energy is converted into heat energy and dissipated, thereby improving the anti-ultraviolet aging performance of the material; the divalent structure formed by pyridine and pyrimidine has a good complexing effect on metals.

[0071] Secondly, the acyl chloride multi-walled carbon nanotubes are grafted onto chitosan. The multi-walled carbon nanotubes have excellent electrical conductivity. When they are evenly dispersed in the coating, they can form a shielding structure in the coating formed by spray painting, effectively preventing the penetration and diffusion of corrosive media and improving the physical anti-corrosion properties of the coating. Chitosan is oxidized by sodium periodate to form a dialdehyde group, and the dialdehyde group reacts with 2-amino-4,6-di-tert-butylphenol to form a Schiff base to obtain modified multi-walled carbon nanotubes. The Schiff base and the adjacent hydroxyl group have a good complexing effect on metal ions.

[0072] Finally, the modified acrylate copolymer, modified multi-walled carbon nanotubes, environmentally friendly solvent, rheological additive, leveling agent, hydroxy acrylic resin, and propellant are placed into the liquid feed end of the two-component aerosol can, and the isocyanate curing agent and solvent are placed into the curing agent end of the two-component aerosol can, and the curing agent end is pressed and shaken to mix evenly to obtain a two-component aerosol spray paint. The metal ligands on the modified acrylate copolymer and the modified multi-walled carbon nanotubes can coordinate and complex with metal ions. For metal substrates, they can undergo physical and chemical adsorption with the metal substrate before corrosion occurs, forming a dense protective film on the surface of the substrate, playing a more excellent physical barrier role. During the corrosion process, they can undergo chelation reaction with free metal ions to form stable organic chelates. Such organic chelates have good compatibility with the coating and are not easy to phase separate, thereby delaying further corrosion.

[0073] Test Example 2:

[0074] Antibacterial performance test:

[0075] The two-component aerosol spray paints prepared in the examples and comparative examples were made into samples according to GB / T 9271-2008, and the antibacterial rates of the samples were tested according to GB / T 21866-2008. The results are shown in Table 2.

[0076] Table 2 Test results of antibacterial properties

[0077] Antibacterial rate Antibacterial rate Example 1 95.91% Comparative Example 1 24.1% Example 2 95.64% Comparative Example 2 95.24% Example 3 96.03% Comparative Example 3 95.47%

[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the two-component aerosol spray paint prepared by the present invention has good antibacterial properties.

[0079] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that first, methyl methacrylate, n-butyl acrylate, and dimethylallylamine are reacted with an initiator to obtain an acrylate copolymer, wherein the dimethylallylamine makes the side chain of the acrylate copolymer have a tertiary amine structure, and the acrylate copolymer is reacted with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer, and the chloromethyl on the chloromethyl (methyl) phosphinoyl chloride reacts with the tertiary amine to form a quaternary ammonium salt with antibacterial properties, which can impart antibacterial properties to the spray paint.

[0080] Test Example 3:

[0081] Flame retardant performance test:

[0082] The two-component aerosol spray paints prepared in the examples and comparative examples were made into samples according to GB / T 9271-2008, and the limiting oxygen index of the samples was tested using a limiting oxygen index instrument according to standard GB / T2406.2-2009.

[0083] Table 3 Test results of limiting oxygen index

[0084] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 28.30 Comparative Example 1 22.41 Example 2 28.32 Comparative Example 2 27.96 Example 3 28.51 Comparative Example 3 28.04

[0085] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the two-component aerosol spray paint prepared by the present invention has good flame retardant properties.

[0086] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that first, methyl methacrylate, n-butyl acrylate, and dimethylallylamine are reacted with an initiator to obtain an acrylate copolymer, wherein the dimethylallylamine makes the side chain of the acrylate copolymer have a tertiary amine structure, and the acrylate copolymer is reacted with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer, and the chloromethyl on the chloromethyl (methyl) phosphinoyl chloride reacts with the tertiary amine to form a quaternary ammonium salt with antibacterial properties, and the introduction of phosphorus element can give the spray paint flame retardant properties.

[0087] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A two-component aerosol spray paint, characterized in that: The invention comprises component A and component B, wherein component A comprises a modified acrylic ester copolymer, a modified multi-walled carbon nanotube, an environmentally friendly solvent, a rheological additive, a leveling agent, a propellant, and a hydroxy acrylic resin; and component B comprises an isocyanate curing agent and a solvent; The modified acrylate copolymer is prepared by reacting methyl methacrylate, n-butyl acrylate and dimethylallylamine under the initiation of an initiator to obtain an acrylate copolymer, reacting the acrylate copolymer with chloromethyl (methyl) phosphinoyl chloride to obtain a quaternized acrylate copolymer; reacting the acrylate copolymer with 5-amino-2-chloropyrimidine to obtain a chloropyrimidinyl acrylate copolymer, reacting the quaternized acrylate copolymer with 3-methoxy-2-(tributylstannyl)pyridine to obtain a pre-modified acrylate copolymer, and finally demethylating the copolymer with boron tribromide to obtain the quaternized acrylate copolymer; The modified multi-walled carbon nanotubes are obtained by grafting chitosan onto acyl chloride multi-walled carbon nanotubes, oxidizing them with sodium periodate, and reacting them with 2-amino-4,6-di-tert-butylphenol.

2. A method for preparing a two-component aerosol spray paint, characterized in that: The method comprises the following preparation steps: (1) Methyl methacrylate, n-butyl acrylate, dimethylallylamine, and toluene are mixed in a mass ratio of 0.5:4:5.5:(20-30), heated to 80-90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuum at 80° C. for 24 hours to obtain an acrylate polymer; (2) mixing an acrylate polymer, triethylamine, chloromethyl (methyl) phosphinoyl chloride, and dichloromethane in a mass ratio of 1: (0.3-0.5): (0.8-0.9): (20-30), heating to 70-80° C., reacting for 12 hours, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, drying the organic layer in air at 45° C. for 12 hours, and then vacuum drying at 50° C. for 20 hours to obtain a quaternized acrylate copolymer; (3) Weighing a quaternary ammonium acrylate copolymer and 5-amino-2-chloropyrimidine in a mass ratio of 1:(1-1.2), mixing the quaternary ammonium acrylate copolymer and dichloromethane in a mass ratio of 1:(20-30) to obtain a quaternary ammonium acrylate copolymer solution, mixing 5-amino-2-chloropyrimidine, triethylamine, and dichloromethane in a mass ratio of 1:(1.2-1.3):(10-12) to obtain a 5-amino-2-chloropyrimidine solution, and adding the 5-amino-2-chloropyrimidine solution dropwise to the quaternary ammonium acrylate copolymer solution at a dropping rate of 1 mL / min. After the dropping is completed, the reaction is continued for 2-3 hours, and a 10 wt % hydrochloric acid solution of 10-12 times the mass of the quaternary ammonium acrylate copolymer is added, and then a saturated sodium bicarbonate solution of 10-12 times the mass of the quaternary ammonium acrylate copolymer is added, and the organic phase is taken and vacuum rotary evaporated to obtain a chloropyrimidinyl acrylate copolymer; (4) 3-methoxy-2-(tributyltinyl)pyridine, chloropyrimidinyl acrylate copolymer, lithium chloride, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.3-0.5):(0.1-0.2):(10-12) and degassed, and 0.1-0.2 times the mass of 3-methoxy-2-(tributyltinyl)pyridine tetrakis(triphenylphosphine)palladium(0) is added, and the temperature is raised to 100° C. to react for 16-18 hours. After the reaction is completed, the pre-modified acrylate copolymer is obtained by rotary evaporation under reduced pressure; (5) Under argon protection, anhydrous and oxygen-free conditions, the pre-modified acrylate copolymer and dichloromethane are mixed in a mass ratio of 1:(50-60), cooled to -20°C, and 0.3-0.5 times the volume of the pre-modified acrylate copolymer of boron tribromide is added dropwise at a rate of 0.5 mL / min. After the addition is completed, the reaction is continued at -20°C for 12 hours. After the reaction is completed, methanol with a volume of 0.1 times that of dichloromethane is added, and then an ice-water mixture with a mass of 3-4 times that of dichloromethane is added, filtered and vacuum dried at 50°C for 20 hours to obtain a modified acrylate copolymer; (6) Pre-modified multi-walled carbon nanotubes, 2-amino-4,6-di-tert-butylphenol, and anhydrous ethanol were mixed in a mass ratio of 1:(4-5):(50-60), refluxed at 78°C for 5-6 hours, cooled to room temperature after the reaction, filtered, washed with anhydrous ethanol for 3-4 times, and finally vacuum dried at 60°C for 12 hours to obtain modified multi-walled carbon nanotubes; (7) Weigh 15-20 parts by mass of a modified acrylate copolymer, 3-5 parts by mass of a modified multi-walled carbon nanotube, 30-40 parts by mass of an environmentally friendly solvent, 0.1-0.5 parts by mass of a rheological aid, 0.1-0.5 parts by mass of a leveling agent, 20-25 parts by mass of a propellant, and 20 parts by mass of a hydroxy acrylic resin; stir the modified acrylate copolymer, modified multi-walled carbon nanotube, environmentally friendly solvent, rheological aid, leveling agent, and hydroxy acrylic resin evenly and grind to a fineness of ≤45 μm, and after grinding, put them into the liquid feed end of a two-component aerosol can, continue to add the propellant and seal the can to obtain component A; weigh 3-5 parts by mass of an isocyanate curing agent and 20-30 parts by mass of a solvent, stir the isocyanate curing agent and the solvent evenly, and after stirring, put them into the curing agent end of a two-component aerosol can and seal the can to obtain component B, press the curing agent end and shake to mix evenly, and obtain a two-component aerosol spray paint.

3. The method for preparing a two-component aerosol spray paint according to claim 2, characterized in that: The initiator solution in step (1) comprises ammonium persulfate and pure water, wherein the mass ratio of ammonium persulfate to pure water is 1:

20.

4. The method for preparing a two-component aerosol spray paint according to claim 2, characterized in that: The preparation method of the pre-modified multi-walled carbon nanotubes in step (6) is as follows: multi-walled carbon nanotubes and 68wt% concentrated nitric acid are mixed in a mass ratio of 1:30, heated to 120°C for reflux reaction for 48h, and then washed with pure water for 7-8 times to obtain carboxylated multi-walled carbon nanotubes; carboxylated multi-walled carbon nanotubes and thionyl chloride are mixed in a mass ratio of 1:20, refluxed at 70°C for 24h, cooled to room temperature, filtered, washed with tetrahydrofuran for 5-6 times, and dried at 50-60°C for 12h to obtain chlorinated multi-walled carbon nanotubes; chitosan is dispersed in N,N-dimethylformamide (30 times the mass of chitosan), allowed to stand for 12h, and chitosan is added under nitrogen protection at a mass of 0 .3-0.5 times of chlorinated multi-walled carbon nanotubes, ultrasonically treated for 2 hours, and then reacted for 96 hours. After the reaction, filtered and washed with 2wt% acetic acid solution for 3 times, filtered with a 0.2μm microporous filter membrane, and finally vacuum dried at 60°C for 12 hours to obtain chitosan grafted multi-walled carbon nanotubes; chitosan grafted multi-walled carbon nanotubes and acetic acid buffer solution with a pH of 3 were mixed in a mass ratio of 1:80, and under nitrogen protection, 5-6 times the mass of sodium periodate aqueous solution of chitosan grafted multi-walled carbon nanotubes were added, reacted at 4°C for 44-48 hours, filtered and washed with pure water for 3-4 times, and finally vacuum dried at 60°C for 12 hours to obtain pre-modified multi-walled carbon nanotubes.

5. The method for preparing a two-component aerosol spray paint according to claim 4, characterized in that: The model of the multi-walled carbon nanotube is L-MWNT-1020; the deacetylation degree of the chitosan is ≥95%.

6. The method for preparing a two-component aerosol spray paint according to claim 4, characterized in that: The sodium periodate aqueous solution is prepared by mixing sodium periodate and water in a mass ratio of 1:

20.

7. The method for preparing a two-component aerosol spray paint according to claim 2, characterized in that: In step (7), the model of the hydroxy acrylic resin is HU56024; the environmentally friendly solvent is propylene glycol ether acetate; the model of the isocyanate curing agent is Basonat HB100; the model of the leveling agent is YCK-1270N; the model of the rheological additive is BYK-7410; the model of the propellant is HFC-134a; and the solvent is acetone.

Citation Information

Patent Citations

  • Antibacterial compositions

    CN101472585A

  • Preparation method of dialdehyde carboxymethyl chitosan

    CN103709267A

  • Stain-resistant and crease-resistant garment fabric

    CN114575163A

  • Biomass antibacterial composite membrane material and preparation method thereof

    CN115028904A

  • Preparation of waterborne polyurethane and application of waterborne polyurethane in waterborne coating

    CN115386098A